PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (KONSUMEN) BERBELANJA PADA INDOMARET PAJJAIANG - Muh. Azis Ardin; Andi Dhika Syafdarifa Guntur (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2021)
This study aims to determine whether there is an influence of factor analysis of the exprential marketing variables, namely the variables sense, feel, think, act, and relate to customer satisfaction in shopping for products in Indomaret Pajjaiang, the sampling method is using a questionnaire. This study uses the Validity Test method. and Reliability Test for Multiple Linear Regression Analysis. Variable simultaneous influencesense(U1), feel(U2)think(U3), act(U4), andRelate(U5)have a significant effect on consumer decisions in shopping for products at Indomaret Pajjaiang.Thiscanbeevidencedfromtheresults of the analysis of the X test Xcount> Xtable (92,231> 2,28) which shows that the influence of the independent variable on the dependent variable in consumer satisfaction shopping for products in Pajjaiang Indomaret is strongly influenced by variables other than research. (sense, feel, think, act, and relate) either partially or simultaneously and positively and significantly effect on the dependent variable, while the most influential variable in consumer shopping decisions is the variable which is the relate that has the highest coefficient of 9,604.